Ultracompact Chip‐Integrated Electromagnetically Induced Transparency in a Single Plasmonic Composite Nanocavity. Issue 4 (6th February 2014) - Chai, Zhen; Hu, Xiaoyong; Zhu, Yu; Sun, Sibai; Yang, Hong; Gong, Qihuang
<x xml:space="preserve">Abstract</x> Ultracompact chip‐integrated electromagnetically induced transparency is realized in a single plasmonic composite nanocavity in plasmonic circuits directly. A small lateral dimension of 600 nm is obtained for the composite nanocavity, which is reduced by one order of magnitude compared with previous reports. A large shift of 490 nm in the transparency window center is obtained through covering poly(methyl methacrylate) layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>